Densification method of screen printed PZT(52/48) thick films - Kim, YB; Kim, TS; Choi, KS; Choi, DJ (TAYLOR & FRANCIS LTD, 2001)
The main problems of the screen printing method are the poor densification and the reaction between the PZT thick films and the Si substrate. For preventing these phenomena, this study adopted hybrid method of screen printing and PZT sol-gel application. PZT(52/48) thick films of 20-40 mum were prepared on Pt/TiO2/YSZ/SiO2/Si substrate. For the sol-gel treated thick films, a remanent polarization of 10.8 to 14.0 muC/cm(2), dielectric constant of 517 to 590, and a piezoelectric constant(d(33)) of 177.0 to 199.9 pC/N were obtained. These results show that the electrical properties of sol-gel treated films is higher than that of only screen printed films. This study shows one of the methods to improve the screen printed thick film's quality and a good solution for the PZT thick film fabrication process on Si-wafer substrate.